Chocolate - Hardy-Gould, Janet (Oxford ; New York : Oxford Univ Press, 2011)
You can drink it, and you can cook with it. You can even make buildings, dresses, hats out of it. You can give it to somebody as a present, or you can buy it for yourself. And of course you can eat it. Dark chocolate, milk chocolate, white chocolate, chocolates with gold on the outside -- everybody loves chocolate.
Stage 2 - 700 headwords.
English language and literature.
Keywords: Chocolate